DNA barcoding of some commonly exploited fishes from the northern Western Ghats, India - QAYOOM, UBAID; PAWAR, RAVINDRA A; MOHITE, SWAPNAJA A; SAWANT, MILIND S; NIRMALE, VIVEK H; PAWAR, SHRIKANT P; GOSWAMI, MUKUNDA; LAKRA, WAZIR S (The Indian Journal of Animal Sciences, 2018)
The Western Ghats, being very rich in freshwater fish diversity, has recently been confirmed as a globallysignificant centre of diversity and endemism for freshwater species and comprise one of the 34 global biodiversityhotspots. Owing to its extreme ichthyofaunal diversity, the present study was designed to generate cytochromeoxidase I (COI) DNA barcodes for the identification of some commonly exploited fishes from the west-flowingrivers of northern Western Ghats. Twenty-three fish specimens representing 6 families and 10 species were barcodedfrom the major west-flowing rivers of the northern Western Ghats. The obtained barcodes discriminated all thespecies with sufficient barcode gap. The average Kimura two parameter (K2P) values for within species, the genusand family distances were 0.37, 17.74 and 18.51% respectively. The neighbour-joining tree revealed distinct clusterscorresponding to the taxonomic status of the species. Generated barcodes are expected to provide the much-neededbaseline reference for the ichthyofaunal biodiversity of the global biodiversity hotspot.